Mitochondria in the Nuclei of Rat Myocardial Cells - Eldarov, Chupalav M. (Cells, 2020)
Electron microscopic study of cardiomyocytes taken from healthy Wistar and OXYS rats and naked mole rats (Heterocephalus glaber) revealed mitochondria in nuclei that lacked part of the nuclear envelope. The direct interaction of mitochondria with nucleoplasm is shown. The statistical analysis of the occurrence of mitochondria in cardiomyocyte nuclei showed that the percentage of nuclei with mitochondria was roughly around 1%, and did not show age and species dependency. Confocal microscopy of normal rat cardiac myocytes revealed a branched mitochondrial network in the vicinity of nuclei with an organization different than that of interfibrillar mitochondria. This mitochondrial network was energetically functional because it carried the membrane potential that responded by oscillatory mode after photodynamic challenge. We suggest that the presence of functional mitochondria in the nucleus is not only a consequence of certain pathologies but rather represents a normal biological phenomenon involved in mitochondrial/nuclear interactions.